Improving the Adherence to Antiretroviral Therapy, a Difficult but Essential Task for a Successful HIV Treatment—Clinical Points of View and Practical Considerations - Iacob, Simona A.; Iacob, Diana G.; Jugulete, Gheorghita (Frontiers in Pharmacology, 2017)
HIV infection caused one of the most devastating human pandemics. The introduction of antiretroviral therapy has changed the course of the pandemic and saved millions of lives. Complex therapeutic schemes have been introduced since 1996 and have contributed to the transformation of HIV infection into a treatable chronic diseases. New types of potent antiretrovirals and their combinations, including “one day” treatment, have simplified the regimens and diminished adverse effects. However, there are still marginalized non-adherent HIV patients (drug users, incarcerated patients, sex workers, social isolated people etc). Many factors can also act after a while or periodically on other populations to lower adherence. The lack of adherence in HIV patients is a multi-factorial and dynamic process and the methods of monitoring have a decreased value or are difficult to apply on the long term. According to current literature, the adherence to antiretroviral therapy is below the required level of 95%, varying between 27-80% in different studies. This finding further highlights the insufficient monitoring and understanding of adherence by HIV patients and health-care providers. Current solutions to this problem are complex. These should be applied by a multidisciplinary team and should be further individualized depending on each population group (children, teenagers, key population, older patients, drug users etc), individual risk factors, patient’s daily routine and drug tolerance. Adherence should be continue and monitored even in patients known to be compliant. In the case of subsequent failure the team should actively identify the reasons for non-adherence. Where usual methods have no chance of success, a coordinated package of services also known as “harm reduction” can be offered in order to reduce the risks of transmission The current article analyses the concept of adherence to antiretroviral therapy, the shortcomings of this medication and the methods that can be applied in practice in order to increase adherence. Emphasis is placed on analysis of the risk groups that currently represent the spearhead with which the HIV pandemic is spreading.